A EDUCAÇÃO A PARTIR DO FEMINISMO NEGRO - Flávia Helena Santos da Silva (TRF2, 2020)
In this article, black feminism is analyzed as an anti-racist tool and a form of contribution to education. Specialized literature of black women and decolonial education was used as a bibliographic base, as well as scientific articles were consulted, selected by searching the Scielo and Google Scholar databases. The study is based on the protagonism and resistance of black women and a means of understanding the formation of black feminism, extracting from this understanding the relevance of the decolonity of knowledge. Thus, situations of black women stand out not only in their daily struggle movements, but mainly in the line of intellectuality, as well as their place of speech and what this movement can contribute to Brazilian education